2014
DOI: 10.1186/s12967-014-0257-3
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of RUNX2 and miR-10a/10b and their inter-relationship in breast cancer

Abstract: BackgroundThe major cancer related mortality is caused by metastasis and invasion. It is important to identify genes regulating metastasis and invasion in order to curtail metastatic spread of cancer cells.MethodsThis study investigated the association between RUNX2 and miR-10a/miR-10b and the risk of breast cancer relapse. Expression levels of RUNX2 and miR-10a/b in108 pairs of tumor and non-tumor tissue of breast cancer were assayed by quantitative PCR analysis and evaluated for their prognostic implications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 45 publications
0
41
0
Order By: Relevance
“…More importantly, miR-10a is found to repress TBX5 protein levels by targeting TBX5 3'UTR. 13) In this study, we predicted Tbx5 to be a potential target of miR-10a using an online database and verified their direct binding by dual-luciferase reporter assay. Examination by qRT-PCR and Western blot showed that both mRNA and protein levels of TBX5 were inhibited by miR-10a, suggesting that miR-10a could not only regulate TBX5 post-transcriptionally, but also decrease the level of Tbx5 mRNA, possibly by affecting mRNA stability.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…More importantly, miR-10a is found to repress TBX5 protein levels by targeting TBX5 3'UTR. 13) In this study, we predicted Tbx5 to be a potential target of miR-10a using an online database and verified their direct binding by dual-luciferase reporter assay. Examination by qRT-PCR and Western blot showed that both mRNA and protein levels of TBX5 were inhibited by miR-10a, suggesting that miR-10a could not only regulate TBX5 post-transcriptionally, but also decrease the level of Tbx5 mRNA, possibly by affecting mRNA stability.…”
Section: Discussionmentioning
confidence: 86%
“…12) Higher expression of miR-10a may be also associated with an adverse outcome in breast cancer. 13) Moreover, it was reported that miR-10a can regulate the proliferation of human cardiomyocyte progenitor cells. 14) miR-10a was shown to be involved in congenital heart disease by targeting T-box 5 (Tbx5), which is a factor participating in embryonic cardiac development.…”
mentioning
confidence: 99%
“…Runt-related transcription factors (Runx 1-3) are key regulators in mesenchymal cell differentiation in osteogenic lineage and of proliferation and differentiation during embryonic development and tissue remodeling (11). In particular, Runx2 is a key regulator of tumorigenesis and functionally linked with tumor progression in breast (12)(13)(14), ovarian epithelial (15), and prostate cancers (16). Activation or increased expression of Runx2, noted particularly in metastatic tumors targeting bone (17)(18)(19)(20), induces an array of genes associated with cell adhesion, invasion, survival as well as increased expression of markers of metastases (21,22).…”
mentioning
confidence: 99%
“…Using the search criteria (Figure 1), a total of 7 publications met the criteria for this analysis (Gee et al, 2008;Radojicic et al, 2011;Liang et al, 2011;Song et al, 2012;Chang et al, 2014;Markou et al, 2014;Parrella et al, 2014). The total number of patients included was 770 ranging from 60 to 219 patients per study.…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…Some concluded that miR-10b expression had no influence on survival (Gee et al, 2008;Radojicic et al, 2011;Parrella et al, 2014), while others reported that miR-10b expression was predictive of decreased survival outcome for breast cancer (Liang et al, 2011;Chang et al, 2014). Insufficient samples and some other factors have resulted in controversial results of different clinical studies.…”
Section: Introductionmentioning
confidence: 99%